Design and Modelling of a Bi – Toroid Transformer - Prumakaram, Kishnu (IRC, 2015)
Bi Toroid transformer is invented for obtaining efficiency beyond 100%. The structure of a Bi Toroid transformer is different from a Conventional transformer because it has one primary coil and two secondary coils. It is designed using two different cores, material wise and size wise. The secondary core is designed to be less reluctance than the primary core. This is done by using larger and higher relative permeability for the secondary core. This will ensure that the secondary core is less reluctance than the primary core. Thus, the induced EMF will not couple back to the primary side. This will ensure that secondary coils induced EMF will follow the less reluctance path. This will boost the efficiency of the transformer past the 100% mark